Expelling the Germans British opinion and post-1945 population transfer in context - Frank, Matthew James, 1973- (Oxford historical monographs., 2007)
An examination of British involvement in the forced migration of German minorities from Poland and Czechoslovakia, this work based on archival research focuses on the refugee crisis caused by this mass movement of population, and on subsequent British attempts to offset its worst effects.